FOOD NOT BOMBS (FNB) SEBAGAI GERAKAN PROTES TERHADAP AKSI MILITERISTIK NEGARA-NEGARA DUNIA - Falhan Hakiki (Dauliyah Journal of Islamic and International Affairs, 2020)
This study aims to determine the Food Not Bombs (FNB) movement as a movement protesting militaristic actions of the states of the world. Through qualitative research methods with analytical descriptive research types and the frameworkof the concept of social movements and international structures as well as the concept of diflusion, FNB action can be identified and explained in its protest against the militaristic actions of world states. The author found the protest action of the FNB was motivated by world states that were too focused on the military field with the fulfillment of military spending, where states were competing to increase the military expenditure so that other sectors were not maximally fulfilled. This has become an established order and the FNB is trying to change that order revolutionarily with the values of pacifism. So the FNB Movement in the international structure have three forms of interaction with the structure itself, first the state system where the FNB is counter to the militaristic system of the states of the world. Second, an international society in which FNB forms solidarity. Third, the world society where FNB is transforming a new form of social order. In this interaction, the FNB carried out its protest actions against the militaristic actions of the states of the world in the form of direct and indirect diflusion. Direct diflusion namely FNB took to the streets in voicing their protest actions and indirect diflusion namely FNB using mass media.